Magneto-optical trapping using planar optics. (29th January 2021) - McGehee, William R; Zhu, Wenqi; Barker, Daniel S; Westly, Daron; Yulaev, Alexander; Klimov, Nikolai; Agrawal, Amit; Eckel, Stephen; Aksyuk, Vladimir; McClelland, Jabez J
Abstract: Laser-cooled atoms are a key technology for many calibration-free measurement platforms—including clocks, gyroscopes, and gravimeters—and are a promising system for quantum networking and quantum computing. The optics and vacuum hardware required to prepare these gases are often bulky and not amenable to large-volume manufacturing, limiting the practical realization of devices benefiting from the properties of cold atoms. Planar, lithographically produced optics including photonic integrated circuits, optical metasurfaces (MSs), and gratings offer a pathway to develop chip-scale, manufacturable devices utilizing cold atoms. As a demonstration of this technology, we have realized laser cooling of atomic Rb in a grating-type magneto-optical trap (MOT) using planar optics for beam launching, beam shaping, and polarization control. Efficient use of available light is accomplished using MS-enabled beam shaping, and the performance of the planar optics MOT is competitive with Gaussian-beam illuminated grating MOTs.